A story of culture and teaching: the complexity of teacher identity formation. Issue 2 (3rd April 2017) - Edwards, F.C.E.; Edwards, R.J.
ABSTRACT: Research in teacher education repeatedly suggests that the background and underlying beliefs held by pre‐service teachers about teaching and assessment act to shape their interpretations of ideas, powerfully influencing their praxis and their developing teacher identity. This paper explores how a young New Zealand secondary science teacher, raised and educated in Māori‐medium and then English‐medium New Zealand schools, develops his identity as a teacher as he navigates a range of educational contexts and experiences. His views on assessment provide a focus. The paper presents a case study drawn from a two‐year longitudinal study, comprising a series of interviews with the teacher, as he transitioned from a university graduate to a qualified science teacher working in his first school. The complexity of teacher identity development is highlighted, particularly for teachers for whom cultural identity and indigenous world view is important. It suggests that beginning teachers need more time in their pre‐service teacher education to reflect on the influence their formative educational experiences have on who they are becoming as a teacher.